The Impact of Poverty, Economic Inequality, and Unemployment on Crime Rates in Central Java Province from 2000 to 2021 - Saiful Adhi Saputra; Wahyu Widodo (Universitas Negeri Semarang, 2023)
In Central Java Province, this study intends to examine how inequality, poverty, and unemployment affect crime. The panel data regression approach is used in this study. The panel regression coefficient for the variable POV in this study was -1.924016 with a probability value of 0.3494, exceeding the significance level of 0.05. These findings demonstrate that the crime variable in Central Java is not significantly impacted by the poverty variable. The panel regression coefficient for the DISP variable is 297.2485, greater than the significance level of 0.05, and has a probability value of 0.0887. These findings support the hypothesis that the inequality variable in Central Java Province between 2000 and 2021 has no appreciable impact on the crime rate variable. With a probability of 0.1089 and a panel regression coefficient of 5.090524 on the UNEMP variable, it can be concluded that the panel regression coefficient above the significance level of 0.05. Based on these findings, it is clear that the crime variable in Central Java Province between 2000 and 2021 is not significantly impacted by the unemployment variable UNEMP. The amount of poverty, inequality, and unemployment in Central Java Province has no discernible impact on crime